Masa depan umat Islam Indonesia : peluang dan tantangan - Amsyari, Fuad (Bandung : al-Bayan, 1993)
Perspectives of Indonesian Muslims
Includes bibliographical references (p. 172)
Keywords: Islam -- Indonesia; Muslims -- Indonesia